International Trade: Commercial policy - J. Peter Neary (University College Dublin, Department of Economics, 2001)
Following a brief historical introduction and a discussion of different types of commercial policy, this paper reviews the arguments for and against trade protection. In the bench-mark case of a competitive, small, open economy, free trade maximizes aggregate national welfare, although some individual groups will lose unless compensation is actually paid. Guidelines for policy include the uniform reduction and concertina rules for tariff cuts, and the principle of targeting: corrective measures should be applied as close to the source of the distortion as possible. Relaxing the bench-mark assumptions allows exceptions to the case for free trade: optimal tariffs to manipulate world prices; strategic tariffs or export subsidies when home firms engage in oligopolistic competition with foreign rivals; and infant industry protection to allow home firms benefit from learning by doing. Protection can also raise the growth rate, though it is less likely to raise welfare in a growing economy. Overall, with due allowance for some ambiguity, both theoretical arguments and empirical evidence suggest a pragmatic case for free trade. Finally, the paper notes the political pressures for and against protection, and the role of international institutions such as the GATT in underpinning moves towards freer trade.
hdl:10197/1251
Keywords: 330; Außenwirtschaftspolitik; Protektionismus; Außenwirtschaftstheorie